ICEAP Proceeding Book Vol 2 2018
DOI: 10.26499/iceap.v2i1.95
|View full text |Cite
|
Sign up to set email alerts
|

UKARA: A Fast and Simple Automatic Short Answer Scoring System for Bahasa Indonesia

Abstract: This paper presents UKARA, a fast and simple automatic short-answer scoring system for Bahasa Indonesia. Automatic short-answer scoring holds an important role in speeding up automatic assessment process. Although this area has been widely explored, only very limited number of previous work have studied Bahasa Indonesia. One of the major challenges in this field is the different type of questions which require different assessments. We are addressing this problem by implementing a combination of Natural Langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…In addition, adding more types of questions besides multiple choices, such as short essays, might enrich the user's learning experience. The implementation of an automatic essay scoring system [10,11] can be used to evaluate the short answer of the player in this game.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adding more types of questions besides multiple choices, such as short essays, might enrich the user's learning experience. The implementation of an automatic essay scoring system [10,11] can be used to evaluate the short answer of the player in this game.…”
Section: Discussionmentioning
confidence: 99%
“…Towards realizing the practical use of SAS systems in the real world, several researchers have explored outputting useful feedback for an input response [21], utilizing rubrics for scoring [19], and investigating adversarial input in SAS [4], to name a few. In addition, research on various languages has also been reported in recent years, including Indonesian [7], Korean [9], and Japanese [15].…”
Section: Previous Researchmentioning
confidence: 99%
“…The second challenge is how we measure the quality of the student's answer. With the growth of natural language processing, it seems not impossible to build a fast response bot that understands the student's question or answer, as research by Herwanto et al that able to achieve an F1 score up to 97,6% [47] [48]. However, the chatbot must empathize with student mistakes, i.e., typos or an almost correct answer.…”
Section: A Scoresmentioning
confidence: 99%